SEVERAL ENTITY ELEMENT IN THE COMPARISON OF AVIATION GEAR BOX CALCULATION - NING ChengFeng; FANG ZongDe; WANG Feng; WANG Xing (Jixie qiangdu)
For effectively calculating the static and dynamic mechanical properties of complex air gear box,use several finite element entity unit type that is commonly used in ANSYS software,then carry out The finite element meshing,static analysis and dynamic analysis on gearbox. The example compare the influence of different type of element unit of the consuming time and the accuracy of the results,give some suggests for the selection of element unit.